2014
DOI: 10.3892/mco.2014.259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors for advanced hepatocellular carcinoma with extrahepatic metastasis

Abstract: Abstract. Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. The aim of this study was to evaluate whether there are differences in the clinical characteristics and survival between patients with advanced HCC with extrahepatic metastasis who received and those who did not receive previous treatment. Between April, 1998 and April, 2012, a total of 419 HCC patients with extrahepatic metastasis (81 previously untreated and 338 previously treated) were enrolled in this study. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 36 publications
(43 reference statements)
4
44
0
Order By: Relevance
“…A retrospective study on 277 HCC patients with extrahepatic metastases demonstrated that by applying local treatment specifically to target intrahepatic lesions to be a significant factor which affected survival of HCC patients with extrahepatic metastases . Aino and his associates showed that in patients who underwent or did not undergo treatment for primary liver cancer, the intrahepatic tumor status was an independent predictor of survival in HCC patients with extrahepatic metastases . The combined modality approach, including the use of PTR, has been shown to result in better prognosis for patients with metastatic disease in other malignancies, such as ovarian, colorectal, and renal carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study on 277 HCC patients with extrahepatic metastases demonstrated that by applying local treatment specifically to target intrahepatic lesions to be a significant factor which affected survival of HCC patients with extrahepatic metastases . Aino and his associates showed that in patients who underwent or did not undergo treatment for primary liver cancer, the intrahepatic tumor status was an independent predictor of survival in HCC patients with extrahepatic metastases . The combined modality approach, including the use of PTR, has been shown to result in better prognosis for patients with metastatic disease in other malignancies, such as ovarian, colorectal, and renal carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have recognised numerous inflammation‐related features in the peripheral blood of HCC patients. Such features include thrombocytosis, leucocytosis, hypoalbuminaemia, increased plasma fibrinogen, relative lymphopaenia, hyperferritinaemia and elevated C‐reactive protein (CRP) …”
Section: Introductionmentioning
confidence: 99%
“…In China, 360,000 incident cases and 350,000 deaths secondary to HCC occur annually [2]. Despite the advance of HCC treatment, metastasis are recovery are quite common in patients underwent resection and thus, the post-operative 5-year survival rate is no more than 40% [3]. The factors leading to the metastasis of HCC, however, are not fully understood, giving rise to great difficulties in predicting the survival time and decisions concerning therapy.…”
mentioning
confidence: 99%